A Web-Based Prognostic Model for Pediatric Genitourinary Rhabdomyosarcoma: Analysis of Population-Based Cohort With External Validation - Li, Jiayi; Huang, Yangyue; Li, Yunpeng; Liu, Pei; Cheng, Haiyan; Song, Hongcheng; Sun, Ning; Shamil, Mina Ayad; Zhang, Weiping (Frontiers in Public Health, 2022)
Background: We conduct an analysis of data from the Surveillance, Epidemiology, and End Results (SEER) database, intending to identify prognostic factors of Pediatric genitourinary Rhabdomyosarcoma (PGU-RMS). Prognostic nomogram and web-based calculator were developed for potential clinical use. Methods: Data of PGU-RMS patients were extracted from SEER database as training and internal validation cohort, patients diagnosed as PGU-RMS from 2001 to 2015 in Beijing Children's Hospital were collected as external validation cohort. We used log-rank tests to seek risk factors on the overall survival (OS) in the overall SEER cohort, tumor site subgroups, radiation subgroups and metastasis subgroups. The univariable and multivariate Cox regression analysis were applied to establish the prognosis model. Results: A total of 372 PGU-RMS patients in SEER and 84 patients from our center were included. 1-, 3-, and 5-year OS of overall SEER cohort were 95.8%, 82.1%, and 78.8%. Subgroup analysis indicated that tumors located in prostate/bladder was associated with the worse prognosis than paratesticular, female genital system and other sites (P<0.001). Tumors of T1/T2 stage, without regional lymph node involved or metastasis can benefit from radiotherapy (P<0.05). For patients without metastasis, younger age, T1/T2 stage, and undergoing radiation were associated with better prognosis (P<0.05). The prognosis nomogram was well-calibrated, the concordance index (C-index) for the OS prediction was 0.823, 0.803 and 0.768 in training, internal and external validation cohort, area under the receiver operating characteristic curve for 3-, and 5-year OS were 0.84, 0.84 in training cohort, 0.90, 0.84 in internal validation cohort and 0.75, 0.80 in external validation cohort. Decision curve analysis showed good clinical utility. The predictive performance of the nomogram was higher than Intergroup Rhabdomyosarcoma Study Group (IRSG) pretreatment stage system based on the comparison of overtime C-index, net reclassification index and integrated discriminatory index (P<0.001). Conclusions: A comprehensive analysis of OS for PGU-RMS patients was conducted based on population cohort. The established prognosis nomogram has been fully validated and evaluated, exhibits better performance than IRSG pretreatment stage system. Furthermore, a web-based risk calculator was developed to optimize clinical decisions.